The role of urban green spaces in mood change. - Abkar, Mahdieh; Mohd Shariff, Mustafa Kamal; Mariapan, Manohar; Maulan, Suhardi; Sheybani, Mehdi (INSInet Publication, 2010)
Urban green spaces have been found as environments that contribute to stress reduction and mood change in several countries such as the West and Taiwan, however there are few studies on people’s perception of the role of urban green space (UGS) in arid regions in Iran. In this study a survey was conducted among visitors of an urban park in the city of Yazd in Iran. They answered questionnaire about use rating and obstacles on the use of UGS, people’s motives for visiting UGS, people’s perception on the effect of UGS on mood change. The results showed that a) lack of green space is one of the greatest obstacle for visiting green space, b) closeness to UGS had a prominent role c) water and green space are two physical features that affect mood change. This research demonstrated the role of visiting UGS on mood change in urban environments; this outcome is usually a basis of positive mood changing disposition and valuable outcomes that are although, nonconsumptive, important in the lives of individuals.